Medullary carcinoma of the breast : role of contrastenhanced MRI in the diagnosis of multiple breast lesions. - Abdul Rashid, Saiful Nizam; Rahmat, Kartini; Jayaprasagam, K. J.; Alli, Kasumawati; Moosa, Fatimah (University of Malaya, 2009)
Medullary carcinoma is a rare breast carcinoma with a syncytial growth pattern and high-grade cytology. It can be difficult to diagnose and may be missed on conventional imaging as the findings may overlap with benign lesions i.e. fibroadenomas. The authors report a case of a 25-year-old female who presented with multifocal breast lumps diagnosed with medullary carcinoma and fibroadenomas. Imaging and pathological correlation with contrast-enhanced MRI are presented in the diagnosis of these lesions.